Regional integration in Latin America : dynamics of the Pacific Alliance - Blanco-Jiménez, Monica; Cruz Alvarez, Jesús (Emerald Publishing Limited, 2019)
The Pacific Alliance treaty has created one of the most competitive and fastest growing economies in the world. In this multi-disciplinary study, authors Monica Blanco-Jiménez and Jesús Cruz Alvarez investigate top industries and the cultural, political and entrepreneurship practices that impact the economic and competitive development of its members.Divided into six parts, the contributors to this volume show the global strategies and synergies that are part of one of the world's most competitive trade zones. Part I explores how this regional integration was build, while Part II presents comparative studies about competitiveness in the automotive industry and Part III offers two studies on Mexico's exports. Part IV, V and VI focus on Peru, Colombia and Chile respectively, looking across social entrepreneurship, corporate social responsibility and social development. Containing the most recent research in international business and relations, this book will help researchers, students and entrepreneurs get to the roots of competitiveness and sustainable growth.